THE USE OF DIGITAL PLATFORM IN LEARNING AND GIVING FEEDBACK ONLINE IN ENGLISH ESSAY WRITING COURSE - Linda Pradita; Fariha Nur Maulida; Rizky Putri Octaviany; Wiwik Mardiana (Program Studi Pendidikan Bahasa dan Sastra Indonesia Universitas Islam Majapahit (UNIM) Mojokerto Indonesia, 2021)
The transformation of face-to-face to online learning becomes a challenge, specifically in teaching English Essay Writing. One of the solutions during online teaching and learning is the use of digital platforms. Moreover, teaching writing needs the process of giving feedback to improve the students’ writing ability. Consequently, integrating technology and feedback strategy becomes our attention. Therefore, this study aims at describing and explaining the digital platform used by the lecturers in teaching activity and feedback process, the lecturer’s and students’ perspectives towards the influence of digital platform in understanding the materials, the integration of digital platform and strategy in giving feedback, and the lecturer’s and students’ perspectives towards the impacts of the application of digital platform and strategy in giving feedback. This research employed interpretive qualitative. The data sources of our research were a lecturer of English Essay Writing and third-semester students of the English Education Study Program at Universitas Islam Majapahit. The results of this study reveal that during online teaching and learning of English Essay Writing, the lecturer applied two kinds of digital platforms such as synchronous (Zoom) and asynchronous (e-learning, YouTube, Powerpoint) and two kinds of feedback strategies (direct and commentary feedback). The use of various digital platforms and feedback strategies are beneficial for the students in understanding the materials. The students’ understanding will also influence the students’ writing ability and quality. Thus, this research recommends the educators implement a combined-digital platform and choose appropriate feedback strategies in teaching writing skills during online learning. Keywords: digital platform, online learning, feedback strategies, english essay writing